Potential Hydrophobic Pocket of Squalene Synthase: An In Silico Analysis - Amelia, Fitri; Hidayat, Basultan; Iryani, Iryani; Iswendi, Iswendi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Cardiovascular disease cases increase due to consumption cholesterol dietary habit. It is well-known that squalence synthase (SQS) is the first committed enzyme for cholesterol synthesis. Therefore, SQS become target of anti-cholesterol. This paper aims to determine the potential binding pocket of SQS (PDB ID: 1EZF). Dogsitescorer, siteFinder, and DEPTH were used for binding pocket prediction and MOE 2009.10 was performed for molecular docking. We found that there are five out of 37 pockets which have druggability score above 0.8. Pocket_5 is the highest drugability and favorable for hydrophobic interaction, yet lower number of hydrogen bond with the ligand. However, Pocket_2, and Pocket_3 are suitable for hydrogen bond formation of ligand-protein. Molecular docking study showed that TAK-475, D99, and Cynarin inhibitors were embedded on the P_2 and P_3 of SQS, showing that P2_and P3 are promising binding pocket for ligand interactions. These results show a promising alternative to design anti-cholesterol using these potential pocket in silico.